LRT System Security Analysis: Threats and Solutions for Implementation in Indonesia - Rizqi Mustafa Maulana; Zaki Azfa AlHafiz; Syahzana Agfah; Nurbo Jatmiko (SAN Scientific, 2025)
The security of the Light Rail Transit (LRT) system is a significant concern as its utilization continues to grow in Indonesia. As a viable solution to urban congestion, the LRT encounters various challenges, including cyberattacks and technical issues that could disrupt operations and jeopardize passenger safety. This study aims to analyze these threats and propose solutions using the ISO-31000:2018 framework. The research employs a Systematic Literature Review (SLR) methodology to assess risks based on their likelihood and potential impact. The findings indicate that the primary threats include phishing attacks, ransomware, and signal system failures. However, this study has limitations, as it is based exclusively on secondary data, which may not fully reflect local conditions. The originality of this research lies in its application of ISO-31000:2018 within the local context and its provision of practical recommendations for operators and policymakers. Moreover, it paves the way for future studies to conduct more comprehensive, field-based research.